KESADARAN DAN SIKAP WARGA MUHAMMADIYAH PAKEM SLEMAN TERHADAP TANGGAP BENCANA; TINJAUAN BUKU FIQIH KEBENCANAAN MUHAMMADIYAH” - Mohamad Muhajir; Yayat Hidayat (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
This study aims to reveal and analyze how the awareness and attitudes of residents, especially Muhammadiyah members of Pakem Sleman DIY, towards the disaster response of the Merapi eruption, in terms of the Fiqh of Disaster book which has been ratified and published by Persyarikatan Muhammadiyah through an official decision to be tagged as the Result of National Conference Tarjih on Fiqh of Disaster.The results of this study are expected to be useful and contribute both practically and theoretically. The practical benefit of this research is that it is hoped that it will be able to provide effective and solutive guidelines for the implementation of worship during the eruption of Mount Merapi, but still based on argumentative arguments and the principles and objectives of Islamic law, one of which is the protection of religion (Hifz ad-Dīn) and guarding the human soul (Hifz an-Nafs). Meanwhile, the theoretical benefit that is expected from this research is to broaden the treasures and discourse of understanding on disaster management according to Muhammadiyah, so that regardless of the circumstances and events that occur in a disaster setting, especially the Mount Merapi Eruption disaster, this guide can be present among Muhammadiyah Pakem Sleman residents to provide assistance. and real solutions in every disaster problem, especially providing a comprehensive understanding of how to respond to disaster phenomena and how to carry out practical procedures for carrying out worship (mahdhah).There are two types of research in this study, namely field research using a qualitative approach and is descriptive in nature. The location of this research is in Pakem District, D.I. Yogyakarta, the subjects of this study were all members of the Muhammadiyah Association consisting of Organization Leaders, Council Leaders, Muhammadiyah Charity Business Leaders whose number was limited based on characteristics. Data were collected by observation, interviews and documentation then analyzed. The second type of research is qualitative by focusing on library research which is analytically descriptive in nature based on the study of the text of the Muhammadiyah Fiqh of Disasters book. The materials contained in the book are basic philosophical understandings about disaster, including practical religious principles according to Muhammadiyah in an emergency situation of a catastrophic disaster, such as the validity of praying in a state of uncleanness and uncovered genitals, or regarding the time limit for multiple prayers during a disaster. understood as a form of difficulty (masyaqqah) and narrowness (haraj). Disaster Jurisprudence understands two general principles: convenience (taysir) and changes in law according to changing situations (tagayyur al-ahkam bi tagayyur al-azminah wa al-amkinah). Islam does not burden beyond human ability.